PELAKSANAAN CORPORATE SOCIAL RESPONSIBILITY PT. ANUGRAHA NIASA SAWINDO DESA ROKAN TIMUR KECAMATAN ROKAN IV KOTO - Jannah, Roudhatul (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Corporate social responsibility is in a moral and moral dilemma, where companies are unethical when enjoying substantial profits, while environment is damaged and society is disregarded or harmed by its rights. In accordance with the core of moral strength is the awareness that is present in the company, it was not able to create awareness of the company to care about the community and the environment, therefore the law entered and made CSR as a mandatory for companies, especially PT. Anugerah Niaga Sawindo which is located in Rokan Timur Village Rokan IV Koto District Rokan Hulu District that existed since 2005. As for the purpose of writing this thesis, namely: First, to find out how the implementation of Corporate Social Responsibility at PT. Anugerah Niasa Sawindo Rokan Timur Village Rokan IV Koto Subdistrict. Second, to find out whether the implementation of corporate social responsibility PT. The award of Niasa Sawindo to the people of Rokan Timur Village Rokan IV Koto Sub-district is in accordance with the laws and regulations.This research is a sociological law research that is research that want to see unity between law and society with existence of gap between das sollen and das sein. This research was conducted in Rokan Timur Village Rokan IV Koto Sub-district Rokan Hulu District, while the population and sample are all parties related to the problem studied in this research, data source used, primary data, and secondary data, data collection technique in research This is done through interviews, literature review and questionnaires.The conclusion of this research is, First Implementation Corporate Social Responsibility PT. Anugrah Niaga Sawindo in Rokan Village, Rokan IV Koto Sub-district has been implemented, the name of its realization The Company only executes not as an obligation as regulated by the Law. Where in running the corporate social responsibility program, the company does not carry out social responsibility in a sustainable manner that can improve the economy of the community. Second In accordance with the provisions of unification Legislation PT. Anugrah Niaga Sawindo in the implementation of corporate social responsibility does not refer to Regional Regulation Riau Province No. 6 of 2012 on Social Responsibility and Environment of the Company. Suggestion writer to the problems studied is the first future in the future PT. Anugrah Niaga Sawindo must carry out corporate social responsibility in accordance with the needs of local communities that provide training, guidance to small and medium micro enterprises and provide guidance to farmer groups to improve the standard of living of the community. Second For the sake of the sustainability of corporate and community development in the environment of PT. Kebun Raja Garden then the company must implement Law Number. 40 Year 2007 regarding Limited Liability Company, Government Regulation Number 47 Year 2012 Concerning Corporate Social Responsibility and Environment Limited, and Riau Province Regional Regulation Number 6 Year 2012 About Corporate Social Responsibility in Riau Province.Keywords: CSR - Society - Economy